Visual complex analysis - Needham, Tristan; Penrose, Roger (Oxford, United Kingdom ; New York, NY : Oxford University Press, 2023)
This new 25th anniversary edition of Visual Complex Analysis introduces this powerful method combining complex numbers with ordinary calculus, and includes new introductory content and brand-new captions that fully explain the geometrical reasoning.--
First edition published 1997.
Includes bibliographical references and index.
Keywords: Functions of complex variables; Mathematical analysis; Mathematics; Functions of complex variables; Mathematical analysis